Faisal’s Nomination for Kingship: British Imperial Interests and Political Realignment in Iraq (1918–1921) - Ranjdar Muhammed Azeez (Journal of Islamic Civilization and Culture Review, 2025)
Following the First World War, Britain played a decisive role in shaping the political order of Iraq and the wider Middle East. Understanding how Faisal was nominated as King of Iraq requires examining the political, military, economic, and diplomatic considerations that guided British imperial strategy during this period. Although historians have studied Britain’s post-war policy in Iraq, many interpretations of the establishment of the Iraqi monarchy rely on incomplete narratives influenced by ideological, ethnic, or political perspectives. This study conducts a historical analysis of British decision-making regarding the Iraqi monarchy by drawing extensively on official British archives and government documents. Through the examination of these sources, the research investigates the context of the 1920 Arab rebellion, the formation of the Iraqi provisional government, and the discussions among British officials concerning possible royal candidates during the Cairo Conference of 1921. The analysis shows that Faisal’s nomination emerged from a combination of imperial strategic interests, regional political considerations, and British assessments of local leadership and stability in Iraq. The study concludes that the selection of Faisal as King of Iraq was not a singular political decision but the outcome of a broader process of imperial strategy and political realignment aimed at stabilizing British influence in post-war Iraq.